Analisis Pengaruh Variasi Diameter Driven Pulley Terhadap Output Kecepatan Putar dan Torsi Akhir pada Trainer Transmisi Toyota Kijang Innova E 2.0 M/T - Febri Panji Diharja; Mochammad Arif Irfa’i; Mohammad Munib Rosadi (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2022)
Pulley is a receiver or converter of rotary power and moment of force associated with each other using a v-belt, while the transmission is a mechanism to convert power from input power to produce variable output power. Torque and RPM are affected by gear ratio or pulley size. The size of pulley on the input shaft also greatly influences torque and RPM. Where necessary to do a trial-driven pulley size. Therefore, this research was conducted to determine the effect of driven pulley size on the output rotational speed and final torque of driven pulley size used. This research uses 3 kinds of driven pulley sizes. Driven pulley 1 (150 mm), the highest torque is 1013.23 Nm and the highest output rotational speed is 1339.5 rpm. In driven pulley 2 (200 mm), the highest torque is 1350.97 Nm and the highest output rotational speed is 1004.62 rpm. While driven pulley 3 (250 mm), the highest torque is 1688.74 Nm, and the highest output rotational speed is 803.7 rpm. In the ANOVA test results, there were no significant differences between the three of pulley diameter variation, indicated by the Sig. 0.395 for output rotational speed and Sig. 0.491 for final torque.